Dynamic response analysis of a reduced scale Kaplan turbine model operating in propeller mode. Issue 1 (1st September 2022) - Escaler, X; Sánchez-Botello, X; Roig, R; De La Torre, O; Mulu, B; Högström, C-M
Abstract: In the frame of the AFC4Hydro H2020 research project, an extensive measurement campaign has been carried out on a reduced scale Kaplan turbine model at the Vattenfall Research and Development facility in Älvkarleby, Sweden. The objective of the tests has been to monitor and characterize the dynamic response of the machine when it operates in propeller mode with a fixed blade angle corresponding to the best efficiency point. A series of measurements have been taken at steady state operating conditions, such as speed no load, part load and best efficiency point, as well as during transient conditions. The turbine has been instrumented with sensors to measure vibrations, displacements, strains and pressures both off-board and on-board. The excitation due to a rotating vortex rope at part load and the structural response induced by it have been clearly measured by the system. A sub-synchronous frequency with a maximum amplitude has been identified for a given part load condition. The evolution of this frequency with the discharge level and the presence of cavitation has been evaluated. Moreover, the response induced by the speed no load condition has been compared against the best efficiency point. Finally, a turbine start-up sequence has been analyzed in the time-frequency domain.